Balancing Security and Liberty: Examining Contemporary Counterterrorism Laws - Masyhar, Ali; Arifin, Ridwan; Sabri, Ahmad Zaharuddin Sani Ahmad (Indonesian Journal of Counter Terrorism and National Security, 2023)
This paper delves into the intricate challenge of striking a delicate balance between national security imperatives and the protection of individual liberties in the context of contemporary counterterrorism laws. In the aftermath of global terrorist threats, governments worldwide have enacted a myriad of legislative measures aimed at preventing and combating acts of terrorism. However, the implementation of these measures often raises concerns about potential encroachments on civil liberties, privacy rights, and due process. The study critically examines the evolving landscape of counterterrorism laws, analyzing key legal frameworks and their impact on individual freedoms. It scrutinizes the delicate equilibrium required to effectively address security threats without sacrificing the fundamental rights and values that underpin democratic societies. Drawing on case studies from diverse jurisdictions, the research explores the implications of counterterrorism measures on marginalized communities, surveillance practices, and the rule of law. Furthermore, the paper assesses the effectiveness of oversight mechanisms and judicial review processes in mitigating the risks of abuse and overreach. It considers the role of technology, international cooperation, and intelligence sharing in contemporary counterterrorism efforts and evaluates their potential impact on individual privacy and human rights. In addition, this paper aims to contribute to the ongoing discourse on counterterrorism policy by offering insights into the challenges of balancing security imperatives with the preservation of civil liberties. It advocates for a thoughtful and nuanced approach that fosters security without compromising the core values that define democratic societies.